Bahasa Inggris - Gibran, El (Yayasan Banu Haji Samsudin, 2023)
This study aims to analyze the effect of the application of integrated information systems on operational efficiency in manufacturing companies in Indonesia. In the digital era, information systems are a vital component in supporting business processes, including in the manufacturing sector which has high complexity. This research uses a qualitative approach with literature study methods and library research. Data was obtained through the study of various scientific journals, academic books, and research reports relevant to the topic of information systems and operational efficiency. The results show that the implementation of an integrated information system is able to improve the efficiency of the production process, reduce operational time and costs, and accelerate data-driven decision-making. The system enables cross-departmental collaboration, real-time data alignment, and information transparency in the supply chain. However, the implementation of information systems also faces challenges such as user resistance, limited technological infrastructure, and the need for human resource training. This research contributes to enriching the literature on information technology in the industrial world, as well as providing strategic recommendations for manufacturing company managers in optimizing the implementation of information systems. It is hoped that the results of this study can be the basis for the development of policies and strategies to improve operational efficiency through the use of information technology more optimally.